2018
DOI: 10.1111/ene.13594
|View full text |Cite
|
Sign up to set email alerts
|

Real‐life long‐term effectiveness of fingolimod in Swiss patients with relapsing‐remitting multiple sclerosis

Abstract: Background and purposeIn 2011, fingolimod was approved in Switzerland for the treatment of relapsing‐remitting multiple sclerosis (RRMS). The aim of the present study was to assess the effectiveness and retention of fingolimod in a real‐life Swiss setting, in which patients can receive fingolimod as both first‐ and second‐line treatment for RRMS.MethodsThis cross‐sectional, observational study with retrospective data collection was performed at 19 sites that comprised both hospitals and office‐based physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
2
2
1
Order By: Relevance
“…The findings that none of our patients developed macular oedema is in agreement with other studies showing a frequency of macular oedema of 0.3% in patients treated with the 0.5 mg dose used in RRMS [4]. The rare occurrence is supported by several post marketing studies emerging in recent years mentioning a total of eight cases of macular oedema amongst almost 2000 patients [11][12][13][14][15][16][17][18][19][20]. The finding of small increases in macular thickness and volume is also in line with a previous study of Nolan et al that showed a small but significant difference in macular volume between MS patients treated with fingolimod and patients never treated with fingolimod [21].…”
Section: Discussionsupporting
confidence: 92%
“…The findings that none of our patients developed macular oedema is in agreement with other studies showing a frequency of macular oedema of 0.3% in patients treated with the 0.5 mg dose used in RRMS [4]. The rare occurrence is supported by several post marketing studies emerging in recent years mentioning a total of eight cases of macular oedema amongst almost 2000 patients [11][12][13][14][15][16][17][18][19][20]. The finding of small increases in macular thickness and volume is also in line with a previous study of Nolan et al that showed a small but significant difference in macular volume between MS patients treated with fingolimod and patients never treated with fingolimod [21].…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this is one of the largest real-world series of patients with RRMS treated with FNG with composite outcomes assessment and for which composite effectiveness outcomes assessment data are available for the 2 years before and after FNG treatment initiation. Similarly to other real-world studies [ 6 , 7 , 11 , 12 , 24 ], patients under FNG treatment maintained a low ARR and thus a high proportion of relapse-free patients, as compared to the pre-FNG period, with a high rate of treatment persistence. Regarding the subgroup analysis, our data showed that FNG brings a benefit on MS patients regardless of the previous DMT used, although to a lesser extent in the NTZ+.…”
Section: Discussionsupporting
confidence: 57%
“…Fingolimod (FNG), proven efficacious in three large phase III trials [1][2][3] and in their extensions [4,5], is a widely used oral medication licensed in the USA for the first-line treatment of relapsing-remitting form of multiple sclerosis (RRMS) and in the European Union (EU) for patients with highly active RRMS defined as either high disease activity despite treatment with at least one disease-modifying treatment (DMT) or rapidly evolving severe RRMS. A large number of postmarketing studies have confirmed the efficacy of FNG in a real-world setting, with data substantially overlapping those of pivotal trials [6][7][8][9][10][11][12][13]. All this despite patients are included in observational studies being on average older, with longer disease duration and more severe neurological disability [14].…”
Section: Introductionmentioning
confidence: 91%
“… 6 19 Acceptable tolerance was observed in the current study. The discontinuation rate was quite low in the current cohort (14.5%) compared with those in previous studies (10.6%–43.8%), 27 28 29 and grade-4 lymphopenia was not considered the main reason for discontinuation.…”
Section: Discussioncontrasting
confidence: 75%